Proliferation of Inhibitory Input to the Substantia Nigra in Experimental Parkinsonism - Faynveitz, Anna; Lavian, Hagar; Jacob, Avi; Korngreen, Alon (Frontiers in Cellular Neuroscience, 2019)
The substantia nigra pars reticulata (SNr) is one of the output nuclei of the basal ganglia (BG) and plays a vital role in movement execution. Death of dopaminergic neurons in the neighboring nucleus, the substantia nigra pars compacta (SNc), leads to Parkinson's disease. The ensuing dopamine depletion affects all BG nuclei. However, the long-term effects of dopamine depletion on BG output are less characterized. In this in-vitro study, we applied electrophysiological and immunohistochemical techniques to investigate the long-term effects of dopamine depletion on GABAergic transmission to the SNr. The findings showed a reduction in firing rate and regularity in SNr neurons after unilateral dopamine depletion with 6-OHDA, which we associate with homeostatic mechanisms. The strength of the GABAergic synapses between the globus pallidus (GP) and the SNr increased but not their short-term dynamics. Consistent with this observation, there was an increase in the frequency and amplitude of spontaneous inhibitory synaptic events to SNr neurons. Immunohistochemistry revealed an increase in the density of vGAT- labeled puncta in dopamine depleted animals. Overall, these results may suggest that synaptic proliferation can explain how dopamine depletion augments GABAergic transmission in the SNr.